Implementation of vehicle routing service - Lee, Samuel Yuru (2017)
The vehicle population in Singapore has been increasing over the past 10 years since 2006 [1] in defiance of various government measures [2] [3] to curb the growth of vehicle population and ensures that the road is not over congested. Thus, it is essential to explore new ways to improve the traffic routing efficacy. One of the ways to improve traffic efficacy is by improving the routing algorithms used by in-car GPS navigator. Currently, many in-car GPS navigator routes O-D by shortest distance. However, static routing does not consider the relation between a direct but congested road and travelling time. This project will explore the degree of traffic efficacy can be improved by dynamic routing. In dynamic routing, navigator will consider the most recent travel time from the start of each edge to its end dynamically. The methodology of this project will use SUMO, an open source Traffic Simulator to simulate a typical busy traffic in Singapore during the peak hours. It is concluded that 2 factors can improve traffic efficacy significantly: • Less frequent Routing • Only small amount of the vehicles may dynamically reroute However, no relation has established over Allocation Strategy and the routing results in this project.